Aplikasi Pengolahan Data Kependudukan Industri 4.0 Berbasis Web - Siti Maesaroh; Ita Erliyani; Yosi Fitria Ningsih (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2020)
The term Industry 4.0 was born from the idea of a fourth industrial revolution. To realize Industry 4.0 academic involvement is needed in the form of research. Currently Industry 4.0 uses conventional information systems, namely recording population data in a master book that has been provided, then recapitulated to make population reports. The system that runs at the Kebon Besar Kelurahan office in Batu ceper Subdistrict currently still has many shortcomings, including requiring a long time in the process of finding data, as well as in the process of making reports. The purpose of this study is to produce a faster and more accurate population data management information system. This research uses data collection methods carried out by observation, literature study and interviews. The results of this study are to facilitate the people in charge of the process of managing population data, assisting in the process of inputting data, searching data, and population reports.